Role of Mujibur Rahman in the Formation of Bangladesh - Bima Pranata Dewantara (ISTORIA: Jurnal Pendidikan dan Sejarah, 2020)
With the formation of Bangladesh, we need to know that there is an important role of Sheikh Mujibur Rahman. Pakistan's concern from politics, economy, social and culture has made the government intervene to reduce the problem. But in fact all of that does not reduce the gap between West Pakistanis and East Pakistanis. On January 6, 1970 AD, Mujibur Rahman was elected President of the Awami League over victory in Pakistan's democratic elections. The Awami League party at a working committee meeting on April 1, 1970 AD decided to take part in the general elections which will be scheduled for later this year. In the general election held on December 7, 1970 AD, Mujibur Rahman demanded the right to draw up a new constitution on the basis of its 6 articles and the right to form a government / cabinet of Pakistan. However, this guidance was rejected by the military regime of President Yahya Khan. As a result, Mujibur Rahman changed his strategy by demanding separation from Pakistan and forming his own country called Bangladesh.